PERANCANGAN SISTEM E-LEARNING BERBASIS ANDROID DENGAN MENGGUNAKAN FIREBASE PADA UNIVERSITAS ADVENT INDONESIA - Hugo Mulana Christon; Elmor Benedict Wagiu; Yulianus Palopak (TeIKa, 2018)
The development of technology is rapidly inreased, especially in the development of smartphones and also learning media. By technology support, various activities can be carried out quickly and easily as well as the activities of the learning and teaching process. The purpose of this study is to analyze and design an E-Learning system that can facilitate students and lecturers at Universitas Advent Indonesia (UNAI) to be able to carry out the learning and teaching process easily. The waterfall model is the SDLC method used in designing and building this system. The results of this study is an Android based e-learning application that can be used to perform tasks such as login/logout, password change, create/delete/change classes and assignments, chat, view user profiles, send announcements, and create new accounts. In the future, it is expected that this application can be linked to the servers of Universitas Advent Indonesia, can provide task notifications before the expiration of the assignment, and improve the user interface so that the display can be more attractive.